The Effectiveness of the educational intervention on professional nurses' person-centred care competence - Pakkonen, Mari (fi=Turun yliopisto|en=University of Turku|, 2024)
Person-centred care is linked to quality of care. The goal of person-centred care is a meaningful life, which is particularly relevant in long-term care, where residents live their everyday lives. This two-phased study aimed to develop a continuing education intervention and evaluate its effectiveness in promoting professional nurses’ person-centred care competence. In Phase I, the ‘Person First - Please’ continuing education intervention was developed based on the literature reviews. In Phase II, i) the level of nurses’ person-centred care competence, their perceptions of person-centred care climate and the relationship between them were investigated by a cross-sectional survey (n = 200 nurses) using validated international instruments; ii) the effectiveness of the intervention was tested using a quasi-experimental design. Cluster sampling was used, including long-term care settings for older people from two cities in the western Finland region. The data were collected from nurses (n = 77 in the intervention group, n = 123 in the control group), residents and their next of kin (n = 18 dyads in intervention units, n = 21 dyads in control units) using validated international instruments at three time points. iii) a mixed-method process evaluation was used to assess the fidelity and acceptability of the intervention implementation. The process evaluation data were collected from nurses in the intervention group using a developed scale (n = 51) and focus group interviews (n = 14). The fidelity of the intervention implementation was observed by nurse managers (n = 3) using a developed structured questionnaire. The data were analysed using statistical methods and content analysis. Person-centred care competence and perceived person-centred care climate were found to be associated. The intervention improved nurses’ person-centred care competence and strengthened the perceived person-centred care climate by the nurses, the residents, and their next of kin. The intervention was implemented as planned and was found to be acceptable. The ‘Person First – Please’ intervention can be an effective way to strengthen nurses’ person-centred care competence and can be implemented in Finnish long-term care units. Further research is needed to conduct a larger-scale study with multiple clusters and a longer follow-up time to ensure the stability of the results.

Koulutusintervention vaikuttavuus hoitajien persoonakeskeisen hoitotyön kompetenssiin Persoonakeskeinen hoitotyö liitetään hoitotyön laatuun. Sen tavoitteena on elämän merkityksellisyys, mikä on olennaista erityisesti pitkäaikaishoidon kontekstissa, jossa asukkaat elävät jokapäiväistä elämäänsä. Tämän kaksivaiheisen tutkimuksen tarkoituksena oli kehittää täydennyskoulutusinterventio ja arvioida sen tehokkuutta edistää hoitajien persoonakeskeisen hoitotyön kompetenssia. Tutkimuksen ensimmäisessä vaiheessa kehitettiin ”Ihminen ensin – kiitos” – täydennyskoulutusinterventio. Toisessa vaiheessa i) Toteutettiin kyselytutkimus, jossa analysoitiin hoitajien persoonakeskeisen hoitotyön kompetenssin tasoa, heidän käsityksiään persoonakeskeisen hoidon ilmapiiristä sekä näiden välistä yhteyttä (n=200 hoitajaa) validoiduilla kansainvälisillä mittareilla. ii) Interventio vaikuttavuutta testattiin kvasikokeellisella asetelmalla käyttäen klusteriotantaa kahden länsisuomalaisen kaupungin pitkäaikaishoidon yksiköistä. Interventiotutkimuksen aineisto kerättiin hoitajilta (n=77 interventioryhmässä, n=123 kontrolliryhmässä), asukkailta ja heidän läheisiltään (n=18 paria interventio-osastoilla, n=21 paria kontrolliosastoilla) validoiduilla kansainvälisillä mittareilla kolmessa aikapisteessä. iii) Monimenetelmäisesti toteutetussa prosessiarvioinnissa interventioryhmän hoitajat (n=51) arvioivat intervention toteutuksen uskottavuutta sekä hyväksyttävyyttä tätä varten kehitetyllä mittarilla ja fokusryhmä-haastatteluilla (n=14). Lähiesihenkilöt (n=3) havainnoivat intervention toteutusta tätä varten kehitetyn strukturoidun lomakkeen avulla. Aineistot analysoitiin tilastollisin menetelmin ja käyttäen sisällön analyysia. Persoonakeskeisen hoitotyön kompetenssi ja koettu persoonakeskeisen hoitotyön ilmapiiri olivat yhteydessä toisiinsa. Interventio kehitti hoitajien persoonakeskeisen hoitotyön kompetenssia, jonka hoitajat, asukkaat ja heidän läheisensä tunnistivat persoonakeskeisen ilmapiirin vahvistumisena. Interventio toteutettiin suunnitellusti ja on hyväksyttävästi toteutettavissa. ”Ihminen ensin – kiitos” -interventio voi olla tehokas keino vahvistaa hoitajien persoonakeskeisen hoitotyön osaamista ja se osoittautui mahdolliseksi toteuttaa suomalaisissa pitkäaikaishoidon yksiköissä. Jatkotutkimusta tarvitaan laajemman tutkimuksen toteuttamiseksi ja pidempää seuranta-aikaa tulosten pysymisen varmistamiseksi.